Primary School Students' Reading Comprehension Ability: Systematic Literature Review - May Yati,; Febrianti, Feni; Mardiah, Anisa Ainul (JURNAL MANAJEMEN PENDIDIKAN, 2026)
The goal of research is to use the systematic literature review (SLR) method to conduct a systematic investigation. "A scientific strategy that limits bias to the systematic collection, critical appraisal, and synthesis of all relevant research studies on a particular topic" is what systematic reviews aim to do. A systematic literature review's main objective is to decrease bias and facilitate improved decision-making by presenting pooled evidence using reliable, pre-established methodologies. in order to compile a thorough understanding of the evaluation of elementary school pupils' reading comprehension abilities. The research topic employed in the study "reading comprehension ability, reading comprehension ability in schools, reading comprehension ability of elementary school students" was determined by the year of publication, education level, class level, and indexing by the international journal Scopus. This study uses a Systematic Literature Review (SLR) design. "A scientific strategy that limits bias to the systematic collection, critical appraisal, and synthesis of all relevant research studies on a particular topic" is what systematic reviews aim to implement. PRISMA is the methodology used in this investigation. PRISMA techniques for meta-analyses and systematic reviews. Meta-analysis use statistical tools to examine combinations of various research items relevant to the same research issue, whereas systematic literature reviews focus on the identification, selection, and critical evaluation of research items. Three steps make up the selection process: inclusion, screening, and identification.Publication statistics over the last five years, from 2019 to 2023, show an annual growth in reading comprehension studies. There was no discernible rise between 2021 and 2022. There were 764 articles about reading comprehension skills in 2023, which is the most study on the subject. Numerous studies have emphasised how crucial it is to start building reading comprehension abilities early on in life as a means of ensuring academic achievement in elementary school. The application of cutting-edge teaching strategies and techniques that can help elementary school-aged children become more proficient readers is also receiving a lot of attention. In order to improve reading comprehension skills, the study suggests conducting more research on expectancy-value theory, including experimental investigations and in-depth qualitative studies involving culturally varied groups